2020
DOI: 10.3892/mco.2020.2137
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of repeat biopsy and detection of cancer after a diagnosis of atypical small acinar proliferation of the prostate

Abstract: Current guidelines recommend a repeat biopsy within 3-6 months after an initial diagnosis of atypical small acinar proliferation (ASAP) due to the high incidence of cancer detection on repeat biopsy. The current study sought to investigate practice patterns after a diagnosis of ASAP in a real-world setting and examine the clinicopathological outcomes of repeat biopsy. The departmental database of the Hyogo Prefectural Nishinomiya Hospital identified 97 of 1,218 patients with a diagnosis of ASAP on initial biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
5
1
Order By: Relevance
“…Almost half of patients with a biopsy diagnosis of ASAP did not undergo repeat biopsy in the follow-up period. This is not dissimilar to other retrospective studies on the outcomes of ASAP [12,15], which show a similar absence of repeat biopsy in a proportion of cases. Other factors that are likely to play a role in the decision to re-biopsy are PSA level/velocity, PSA density, results of mpMRI, patient age, and indeed patient preference, following discussion with the urologist of all the available information.…”
Section: Discussionsupporting
confidence: 65%
“…Almost half of patients with a biopsy diagnosis of ASAP did not undergo repeat biopsy in the follow-up period. This is not dissimilar to other retrospective studies on the outcomes of ASAP [12,15], which show a similar absence of repeat biopsy in a proportion of cases. Other factors that are likely to play a role in the decision to re-biopsy are PSA level/velocity, PSA density, results of mpMRI, patient age, and indeed patient preference, following discussion with the urologist of all the available information.…”
Section: Discussionsupporting
confidence: 65%
“…Warlick et al 15 have reported that 17.3% of men have GS ≥ 7 following a TRUS biopsy for ASAP. Yoshida et al 16 reported relatively high csPCa detection rate (13/16 PCa patients, 81.6%) but their study resulted from smaller number of total PCa patients than ours. They indicated that decision making for a repeat biopsy could be affected by clinical characteristics like a small prostate ( p = 0.0250) and advanced age ( p = 0.0297) in real-world settings.…”
Section: Discussioncontrasting
confidence: 62%
“…ASAP, a pathological entity defined as the proliferation of small acini without sufficient histological atypia to warrant a definitive diagnosis of prostate adenocarcinoma, is seen in 1.5–9% of primary prostate biopsies [ 16 18 ]. The presence of this lesion may be a source of concern for both the pathologist and the urologist in terms of making the correct diagnosis, detecting the cancer and determining follow-up intervals.…”
Section: Discussionmentioning
confidence: 99%